Impact of comorbidities and drug therapy on development of renal impairment in a predominantly African American and Hispanic HIV clinic population - M Keith Rawlings (Dove Medical Press, 2011)
M Keith Rawlings1, Jennifer Klein1, Edna P Toubes Klingler1, Ejeanée Queen1, Lauren Rogers1, Linda H Yau2, Keith A Pappa2, Gary E Pakes21AIDS Arms Peabody Health Clinic, Dallas, Texas; 2GlaxoSmithKline, Research Triangle Park, North Carolina, USAPurpose: Renal impairment in human immunodeficiency virus (HIV)-infected patients could potentially be caused by many factors. HIV-related renal impairment risks have been little studied in African Americans and Hispanics. We investigated the impact of HIV itself, highly active antiretroviral therapy (HAART), comorbidities, and non-HIV-related drug treatment on glomerular filtration rate in a predominantly African American/Hispanic HIV-infected population who had received HAART for at least one year. This study was a retrospective electronic medical record database evaluation of renal impairment risks in a largely African American/Hispanic HIV population obtaining medical care at an HIV clinic in Dallas, Texas.Methods: Proportional hazards models were used to investigate an association between an estimated glomerular filtration rate decrease >25% from baseline (ie, renal impairment) and demographics, antiretroviral/nonantiretroviral medications, comorbidities (hypertension, diabetes mellitus, hepatitis C virus [HCV] infection, hepatitis B virus [HBV] infection), CD4+ counts, viral load, and duration patients were monitored at the clinic (time on study).Results: In total, 323 patients were evaluated: 82% males; 61% African American/12% Hispanic/19% Caucasian; mean age 37.9 years (standard deviation [SD] 8.5); 6% HBV-positive; 34% HCV-positive; 29% hypertensive; 3% diabetic; 52% tenofovir-treated; mean weight 75.4 kg (SD, 15.4); mean estimated glomerular filtration 114.5 mL/min/1.73 m2 (SD, 36.7) using the Modification of Diet in Renal Disease (MDRD) calculation method; mean creatinine clearance (from which estimated glomerular filtration was extrapolated) by the Cockcroft-Gault calculation method 120.6 mL/min/1.73 m2 (SD, 41.2); mean time on study 2.7 years (SD, 1.0 year). An estimated glomerular filtration rate decrease of . >25% from baseline was significantly associated with time on study (P = 0.0017; hazards ratio [HR] = 0.999) and hypertension (HR = 1.706; P = 0.0158) by the MDRD method, and with age (HR = 1.039; P = 0.0077), weight (HR = 0.987; P = 0.0023), and time on study (HR = 0.999; P = 0.0043) by extrapolation of Cockcroft-Gault creatinine clearance calculation. No specific HAART agent was associated with significant renal impairment risk by the definition used in this study.Conclusion: This retrospective database study showed time on study, hypertension, weight, and age to be the only significant predictors of an estimated glomerular filtration rate decrease >25% from baseline.Keywords: nephropathy, antiretroviral therapy, comorbidities, tenofovir, African American, Hispanic